The increased prevalence of depression and anxiety in T2DM patients associated with blood glucose fluctuation and sleep quality - Wei Yang; Min Liu; Yuan Tian; Qianwei Zhang; Jiahua Zhang; Qiaoyun Chen; Lixia Suo; Yang Chen (BMC Endocrine Disorders, 2022)
Abstract Background Current evidence demonstrates that blood glucose fluctuation can be associated with depression and anxiety. The association among blood glucose fluctuation, traditional risk factors and emotional disorders in T2DM should be studied and clarified. Methods A total of 182 diabetic patients including 81 patients with depression or anxiety and 101 patients without emotional disorder were enrolled into this study. Data were obtained through medical history and questionnaire survey. Data were analyzed using appropriate statistical methods. Results The comparison results of basic information between the two groups showed that the differences of the proportion of female were statistically significant (p = 0.002). There was no statistical difference in laboratory examination indexes between the two groups, however, standard deviation of blood glucose (SDBG) and postprandial glucose excursion (PPGE) of the comorbidity group were significantly higher than that of control group (p = 0.032 and p = 0.037). The results of questionnaire survey showed that there were statistically significant differences in sleep quality, PSQI and dietary habit between the two groups (p < 0.001, p < 0.001 and p < 0.001). Stratified analysis results according to gender showed that the percentage of cognitive disorder, anxiety and depression in female group was significantly higher than that in male group (p = 0.001, p < 0.001 and p < 0.001). Mini-mental state examination (MMSE), self-rating anxiety scale (SAS) and patient health questionnaire (PHQ-9) score in female group were also higher than male group (p = 0.001, p < 0.001 and p < 0.001). Logistic regression analysis results showed that SDBG and sleep quality were associated with emotional disorders in T2DM (p = 0.040 and p < 0.001) and the OR values of these factors were 7.588 (1.097–52.069) and 4.428 (2.649–7.401). Conclusions Blood glucose fluctuation and sleep quality are associated with the increased prevalence of depression and anxiety disorders in T2DM.